The phenotype of 15 cases with rare 8q24.13‐q24.3 deletions–A new syndrome or still an enigma?. Issue 5 (22nd February 2021) - Maya, Idit; Kahana, Sarit; Agmon‐Fishman, Ifaat; Klein, Cochava; Matar, Reut; Berger, Racheli; Josefsberg, Sagi Ben Yehoshua; Shohat, Mordechai; Marom, Daphna; Basel‐Salmon, Lina; Sagi‐Dain, Lena
Abstract: Diagnosis of rare copy number variants (CNVs) with scarce literature evidence poses a major challenge for interpretation of the clinical significance of chromosomal microarray analysis (CMA) results, especially in the prenatal setting. Bioinformatic tools can be used to assist in this issue; however, this prediction can be imprecise. Our objective was to describe the phenotype of the rare copy number losses encompassing the 8q24.13‐q24.3 locus, and to find common features in terms of genomic coordinates, gene content, and clinical phenotypic characteristics. Appropriate cases were retrieved using local databases of two largest Israeli centers performing CMA analysis. In addition, literature and public databases search was performed. Local database search yielded seven new patients with del (8)(q24.13q24.3) (one of these with an additional copy number variant). Literature and public databases search yielded eight additional patients. The cases showed high phenotypic variability, ranging from asymptomatic adults and fetuses with normal ultrasound to patients with autism/developmental delay (6/11 postnatal cases, 54.5%). No clear association was noted between the specific disease‐causing/high‐pLI gene content of the described del (8)(q24.13q24.3) to neurodevelopmental disorders, except for a possibly relevant locus encompassing the KCNQ3 gene. We present the challenges in classification of rare variants with limited clinical information. In such cases, genotype–phenotype correlation must be assessed with extra‐caution and possibly using additional methods to assist the classification, especially in the prenatal setting.